Contextual contracts for component‐oriented resource abstraction in a cloud of high performance computing services. (24th February 2021) - de Carvalho Junior, Francisco Heron; Al‐Alam, Wagner Guimarães; de Oliveira Dantas, Allberson B.
Summary: Efforts to support high performance computing (HPC) applications' requirements in the context of cloud computing have motivated us to design HPC Shelf, a cloud computing services platform to build and deploy large‐scale parallel computing systems. We introduce Alite, the contextual contract system of HPC Shelf, to select component implementations according to requirements of the host application, target parallel computing platform characteristics (e.g., clusters and MPPs), quality of service (QoS) properties, and cost restrictions. It is evaluated through a small‐scale case study employing two complementary component‐based frameworks. The first one aims to represent components that implement linear algebra computations based on the BLAS interface. In turn, the second one aims to represent parallel computing platforms on the IaaS cloud offered by Amazon EC2 Service.